Long-term (16–26 years) follow-up outcome of steroid therapy in refractory autoimmune sensorineural hearing loss. Issue 121 (July 2021) - Nishimura, Tadashi; Okayasu, Tadao; Hosoi, Hiroshi; Kitahara, Tadashi
Abstract: Autoimmune sensorineural hearing loss (ASHL) is a rare disease of uncertain etiology, with no established treatment strategy. The duration of morbidity is increased in refractory cases; and therefore, the preservation of hearing and the prevention of adverse effects with steroid therapy are serious long term issues to consider. Long-term follow up of patients treated for ASHL was performed retrospectively in order to elucidate the pathogenesis of ASHL, evaluate the consequences of steroid therapy, and determine a promising treatment course. The cohort in this study consists of four female patients with refractory ASHL that were followed for 16–26 years. Three patients already had profound deafness on one side, probably due to ASHL, before the initiation of steroid treatment. ASHL was managed with steroid administration and the hearing was evaluated through regular audiometric tests (173–212 times). The relationship between pure tone threshold average and steroid dose was reviewed over a long-term follow-up period for each patient. During follow-up, hearing deficit progressed rapidly several times in all patients, as did responsiveness to steroid therapy. Long-term high-dose steroid therapy was not required for hearing maintenance. Hearing thresholds were nearly maintained in three patients during the 16- to 21- year follow-up, and gradually declined over a 26-year follow-up period in one patient. Considering the progress due to presbycusis, the maintenance of hearing was considered sufficient in all patients. No serious adverse effects were observed in any of the patients. Management of patients affected by ASHL with regular audiometry allowed for hearing maintenance without the morbidity of prolonged steroid therapy. The current observations give insight into the pathogenesis of ASHL pathogenesis and establish an efficient course of treatment. Highlights: Long-term follow-up of 4 patients with autoimmune sensorineural hearing loss (ASHL). Repeated audiometric tests were used for managing steroid treatment. Long-term high-dose steroid therapy was not required for hearing maintenance. Disease activity was suppressed during pregnancy in one patient. ASHL treatment needs to be personalized for each patient.